2010
DOI: 10.1021/jp102044u
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assemblies of 1,4-Benzene Diboronic Acid on KCl(001)

Abstract: The self-assembly of benzene diboronic acid molecules on KCl(001) is investigated at room temperature by means of non-contact Atomic Force Microscopy. When depositing the molecules on the freshly cleaved surface, the molecules self-assemble into an extended twodimensional supramolecular phase driven by H-bonds. Theoretical calculations based on Density Functional Theory show that the cohesion energy of the structure yields almost 1 eV per molecule. In combination with high-resolution structural analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…The characterization of these interfaces from a structural and an optical point of view down to the molecular scale is challenging and requires analytical methods with high sensitivity in an ultrahigh-vacuum (UHV) environment. On the one hand, scanning probe techniques, such as atomic force microscopy (AFM) in noncontact mode (nc-AFM), can provide access to the structure of the adsorbed molecular layers down to the molecular scale [19][20][21][22][23] and beyond [24][25][26][27][28][29]. The nc-AFM method, particularly on bulk insulators and at room temperature is demanding.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of these interfaces from a structural and an optical point of view down to the molecular scale is challenging and requires analytical methods with high sensitivity in an ultrahigh-vacuum (UHV) environment. On the one hand, scanning probe techniques, such as atomic force microscopy (AFM) in noncontact mode (nc-AFM), can provide access to the structure of the adsorbed molecular layers down to the molecular scale [19][20][21][22][23] and beyond [24][25][26][27][28][29]. The nc-AFM method, particularly on bulk insulators and at room temperature is demanding.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] The formation of organic layers on insulators has been achieved in the past by either strengthening the molecule-surface (M-S) interaction by means of appropriate anchoring groups, [ 17,18 ] or by reinforcing the molecule-molecule (M-M) interaction. [ 19,20 ] Several attempts have also been made to infl uence the balance between M-S and M-M interactions. [21][22][23] However, achieving control over structural characteristics of large-scale supramolecular networks, such as e.g., pore size, proved challenging.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] A second strategy involves educated molecular design. Some molecules are able to form wire structures through π-stacking, [ 27,28 ] other examples include stabilization of the molecular layers via hydrogen bonding, [ 19 ] and a few experiments report on the use of polar groups to enhance adsorption onto ionic substrates. [ 17,29,30 ] However, there is no single set of design criteria for the morphology and stability of such fi lms that can satisfy a wide range of possible applications.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilizing effect of intermolecular hydrogen bonds has, furthermore, been exploited in a recent study utilizing the unusually strong intermolecular cohesion energy of boronic acid to stabilize a wetting layer on KCl(001) at room temperature 86. In this study, the substrate has been shown to have a marginal influence on the resulting molecular film, illustrating that the strong intermolecular cohesion rather than the molecule‐surface adhesion is responsible for the stabilization of the film.…”
Section: From Bulk Structure Formation To Substrate Templatingmentioning
confidence: 84%